Bicyclol Regulates Hepatic Gluconeogenesis in Rats with Type 2 Diabetes and Non-alcoholic Fatty Liver Disease by Inhibiting Inflammation - Li, Hongxue; Xu, Qian; Xu, Chengye; Hu, Yuxin; Yu, Xingyang; Zhao, Kangqi; Li, Mingqing; Li, Meng; Xu, Junfang; Kuang, Hongyu (Frontiers in Pharmacology, 2021)
Hepatic gluconeogenesis plays an important role in maintaining the body's glucose metabolism homeostasis. Non-alcoholic fatty liver disease (NAFLD) is the most common cause of chronic liver diseases, When combined with type 2 diabetes mellitus(T2DM), it can cause severe glucose metabolism disorders. Studies have confirmed that chronic liver inflammatory lesions are the basis of T2DM combined with NAFLD. Inhibiting liver inflammation can improve glucose metabolism disorders. It is essential to explore safer and effective drugs to inhibit liver inflammation to improve the body's glucose metabolism disorders. In the present study, the hepatoprotective effects and underlying mechanisms of bicyclol in T2DM-NAFLD were investigated. T2DM-NAFLD and bicyclol treatment models were established. The results revealed that bicyclol alleviated fasting blood glucose, serum transaminase levels, insulin resistance, hepatic adipogenesis, lipid accumulation and markedly reduced T2DM‐NAFLD rat histological alterations of livers. Not only that, bicyclol markedly attenuated T2DM-NAFLD induced production of inflammation factors (IL-1β and TNF‐α). Moreover, bicyclol suppressed the expression of insulin/gluconeogenesis signaling pathway (Akt, PGC-1α and PEPCK).These findings suggested that bicyclol might be a potentially effective drug for the treatment of T2DM-NAFLD and other metabolic disorders .